Tannin extract of acacia mearnsii for lactating ewes Extrato tanífero de acacia mearnsii para ovelhas em lactação - Hans Dallastra L.J.* (2018)
© 2018 Universidade Estadual de Londrina. All rights reserved.Condensed tannins can reduce protein degradation in the rumen by increasing the duodenal flow of metabolizable proteins and consequently improving animal performance. The objective of this study was to evaluate the effect of the tannin extract of Acacia mearnsii on lactating ewes receiving a total mixed ration (TMR) containing two concentrations of crude protein. The experimental treatments consisted of a TMR containing 16.4% or 22.3% of crude protein in dry matter either with or without the tannin extract of Acacia mearnsii at 20 g kg-1 dry matter. The extract concentration that guaranteed the daily intake of approximately 15 g of the extract per animal was determined. Eight lactating ewes of the Texel × Lacaune breed in the second third of lactation were distributed in a 4 × 4 Latin square experimental design, with four periods of 19 days, including 14 days of adaptation and 5 days of sample collection. Urinary nitrogen excretion was increased in the animals fed a diet containing a relatively higher protein concentration compared to those receiving a diet with a lower protein concentration. However, milk production and the concentration of milk solids did not vary significantly among treatments. The tannin extract of Acacia mearnsii decreased urinary nitrogen excretion, and consequently reduced the environmental impact of the production system, but did not significantly improve animal performance.